2019
DOI: 10.1371/journal.pone.0217874
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal complications following on-pump cardiac surgery—A propensity matched analysis

Abstract: Background Gastrointestinal complications following on-pump cardiac surgery are orphan but serious risk factors for postoperative morbidity and mortality. We aimed to assess incidence, perioperative risk factors, treatment modalities and outcomes. Material and methods A university medical center audit comprised 4883 consecutive patients (median age 69 [interquartile range IQR 60–76] years, 33% female, median logistic EuroScore 5 [IQR 3–11]) undergoing all types of cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 21 publications
4
37
0
3
Order By: Relevance
“…The ECC time is an established risk factor for GI complications. 24,25 The present study provides evidence for the hypothesis that GI dysfunction precedes GI complications since more than 60% of the patients in the AGI !2 group later developed GI complications. The overall incidence of acute mesenteric ischemia was 0.4%, which is in line with previous studies.…”
Section: Discussionsupporting
confidence: 52%
“…The ECC time is an established risk factor for GI complications. 24,25 The present study provides evidence for the hypothesis that GI dysfunction precedes GI complications since more than 60% of the patients in the AGI !2 group later developed GI complications. The overall incidence of acute mesenteric ischemia was 0.4%, which is in line with previous studies.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies have shown a strong correlation between preoperative EuroSCORE values and GI complications. 44,45 It is therefore essential that preoperative risk assessment is carried out, so both patients and staff are prepared to deal with any subsequent complications. Preexisting GI conditions such as ulcers and hemorrhoids have also been found to be associated with a higher rate of upper and lower GI bleeding, respectively.…”
Section: Preoperativementioning
confidence: 99%
“…Preexisting GI conditions such as ulcers and hemorrhoids have also been found to be associated with a higher rate of upper and lower GI bleeding, respectively. 44 Other methods to potentially reduce the risk of complications include the use of a PPI to reduce the risk of duodenal and peptic ulcers. In a randomized controlled trial including 210 patients undergoing cardiac surgery, those who were administered a PPI had fewer active ulcers (4.3%) compared to patients given histamine type 2 receptor antagonists (21.4%) or a mucosal protector (28.6%).…”
Section: Preoperativementioning
confidence: 99%
See 1 more Smart Citation
“…Gastrointestinal (GI) complications are uncommon, but potentially highly morbid events following cardiac surgery procedures 1 . The reported incidence of these events is between 0.5% and 4.5% of cardiac cases, but the in‐hospital mortality associated with GI complications is around 30%–40%, with some series reporting higher rates of mortality 2–8 . Previous series have identified several risk factors such as increasing age and comorbidity, as well as and prolonged operation times as risk factors for the development of GI complications 3,4,7 .…”
Section: Introductionmentioning
confidence: 99%